Les Les systèmes de retraite par répartition ont-ils créé le mal qui les ronge ? - BAIDANE, Abdelaziz (Revue Internationale du Chercheur, 2020)
It is common to consider that the fall in the birth rate and the population aging are the major cause of the imbalances that shake pay-as-you-go pension systems. Rather, this paper seeks to support the idea that pay-as-you-go pension systems are in fact the product of a vicious conception that would be at the origin of the fall in the birth rate which eventually suffocated them. They themselves would have created the evil that gnaws at them.